A Clinical-Statistical Study on COVID-19 Cases in Iraq: A Case Study - Raheem, Rasha; Kadhom, Mohammed; Zuheir Alhashimie, Enas; Abdul-Jabbar Alrubayee, Wathik; Albayati, Noor (Al-Nahrain Journal of Science, 2021)
Background: COVID-19 is a disease that started in Wuhan/China in late 2019 and continued through 2020 worldwide. Scientists worldwide continue to research to find vaccines, treatments, and medication for this disease. Studies also conenue to find the pathogenicity and epidemiology mechanisms.Materials and Methods: In this work, we analyzed cases obtained from Alshifaa center in Baghdad/Iraq for 23/2/2020-31/5/2020 with total instances of 797, positive cases of 393, and death cases of 30.Results: Results showed that the highest infection cases were among people aged between 41-45. Also, it was found that males' number of cases was more than females. In contrast, death cases were significantly higher in males than females. It was notable that the number of cases increased over time; here, it grew from April to May from 92 to 238, respectively.Conclusion: It is worth mentioning that by the beginning of Jun, the number of cases has dramatically increased, and now more than 2K points are recorded daily. Also, death cases had the same behavior.